Dendritic cell development: A personal historical perspective. (March 2020) - Shortman, Ken
Abstract: Dendritic cells(DCs) were once considered as a single cell type closely related developmentally to macrophages. Now we recognise several subtypes of DCs and have outlined several different pathways that potentially lead to their development. This article outlines some of the research findings that led to these changes in perspective, from the point of view of one of the participants.